2015
DOI: 10.1590/s0036-46652015000100006
|View full text |Cite
|
Sign up to set email alerts
|

STUDY OF THE PREVALENCE OF Capillaria hepatica IN HUMANS AND RODENTS IN AN URBAN AREA OF THE CITY OF PORTO VELHO, RONDÔNIA, BRAZIL

Abstract: Introduction: Hepatic capillariosis, caused by Capillaria hepatica (Calodium hepaticum) (Bancroft, 1893), Travassos, 1915 (Nematoda, Trichinelloidea, Capillariidae), is a common zoonosis in rodents but is rare in humans. Seventy-two cases in humans have been reported worldwide since the first case was described by MACARTHUR in 192417,27. This study aimed to determine the prevalence of Capillaria hepatica in humans and rodents in an urban area of Porto Velho, the capital of Rondônia, in Brazil. Methods: After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In order to determine the real status of these parasites, conducting more studies in other parts of Iran is required. The rats captured for the study of Capillaria infection were infected similar to studies reported in other parts of the world, including Milan, Italy, 24 Baltimore, Maryland, 30 Brazil, 31 Switzerland, 25 and Egypt. 32 In addition, the rats captured from Sanandaj showed partial resistance to this nematode since they were heavily infected, without showing apparent clinical signs and had fibrous clusters of eggs in one part of their liver as well as active infection of live adult worms in other parts ( Figure 3C).…”
Section: Discussionmentioning
confidence: 53%
“…In order to determine the real status of these parasites, conducting more studies in other parts of Iran is required. The rats captured for the study of Capillaria infection were infected similar to studies reported in other parts of the world, including Milan, Italy, 24 Baltimore, Maryland, 30 Brazil, 31 Switzerland, 25 and Egypt. 32 In addition, the rats captured from Sanandaj showed partial resistance to this nematode since they were heavily infected, without showing apparent clinical signs and had fibrous clusters of eggs in one part of their liver as well as active infection of live adult worms in other parts ( Figure 3C).…”
Section: Discussionmentioning
confidence: 53%
“…This is the first published report of C. hepaticum prevalence in R. norvegicus from Salvador since 1976 when carriage in captured rats was 57% [6]. The carriage level of 83% determined by this study is higher than the most recent documentations of C. hepaticum in R. norvegicus from cities in Brazil: Rio de Janerio (47%) [8] and Porto Velho (2%) [7]. This is potentially due to the high host density and year round conditions suitable for egg embryonation.…”
mentioning
confidence: 55%
“…Infectious rodents with this nematode have been reported by Kia et al 31 and Zarei et al 51 from the northwest, Moradpour et al 17 from the east and west, and Pakdel et al 27 and Kazemi et al 52 from western regions of Iran. Regarding the hosts, almost 80 species of rodents in the family Muridae, as well as about 24 species of mammals, including humans, could be infected with this parasite [53][54] .…”
Section: Discussionmentioning
confidence: 99%